Museum representations of Chinese diasporas : migration histories and the cultural heritage of the homeland - Wang, Cangbai (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"The Overseas Museums of China is the first book to analyse the recent upsurge in these types of museums. Examining heritage-making beyond the conventional framework of the nation-state, the book provides a much-needed, critical examination of China's engagement with its diasporic communities. Drawing on fieldwork in more than ten museums, as well as interviews with museum practitioners and archival study, Wang offers a timely analysis of the complex ways in which Chinese diasporas are represented in the museum space of China, the ancestral homeland. Arguing that diasporic heritage is highly ambiguous and introducing a diasporic perspective to the study of cultural heritage, this book opens up a new avenue of inquiry into the study and management of cultural heritage in China and beyond. Most importantly, perhaps, Wang sheds new light on the dynamic between China and Chinese diasporas through the lens of the museum. The Overseas Museums of China takes a transnational perspective that will draw attention to the under-researched connections between heritage, mobility and meaning in a global context. As such, this cross-disciplinary work will be of interest to scholars and students working in the museum and heritage studies fields, as well as those studying Asia, China, migration and diaspora, anthropology, history and culture"--
The birth of the Overseas Chinese History Museum of China -- The representation of the Chinese diasporas as a 'national self/other' -- Negotiating 'hot' and 'cool' authentication in heritage-making at a qiaoxiang -- Repatriation of Chinese cultural relics as a site for place-making and identity construction -- The stamps of identity: Negotiating trans-local subjectivities in philatelic space -- How does a house remember? Materialising memories of return migration at a huaqiao farm -- The im/possibility of museumifying the Chinese diasporas in South China.
OCLC-licensed vendor bibliographic record.
Keywords: Zhongguo Hua qiao li shi bo wu guan -- History; Chinese diaspora -- Museums -- China -- History; Museums -- China -- History -- 21st century